Perbandingan Corporate Social Performance pada Bank Umum Syariah di Indonesia Periode 2013-2016 - Renata Amelia Soegiharto; Atina Shofawati (Universitas Airlangga, 2019)
This study is aimed to determine the difference in social performance of Islamic Banks period 2013-2016. The quantitative approach of purposive sampling is used as the research method. This study takes a sample of Islamic banks in Indonesia which is tested into twelve Sharia Commercial Banks. Analysis of different test using ANOVA and Kruskal-Wallis test. The ratio assessment of social performance was analyzed using fiveteen variables: MMR, AR, KPJP, PFA, QR, ZR, RFS, CSR, KSM, KM, KI, KPW, KPP, PKSR, and R&D. The data used is secondary data gathered financial report in period 2013-2016. The Comparative analysis result in all social performance ratios showed differences in social performance of Islamic bank, except in ratio of CSR showed no significant differences.Keywords: Social Performance, Islamic Banks, Comparative Analysis, CSPREFERENCES Al-Jawziyyah, I.Q. 1995. I’lam al-Muwaqqi’in. KaherahAlma, Buchari dan Donni Juni Priansa. 2009. Manajamen Bisnis Syariah. Bandung: AlfabetAnshori, Muslich dan Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press.Antonio, M.Syafi’i. 2001. Bank Syariah, Dari Teori Ke Praktik. Jakarta: Gema InsaniDendawijaya, Lukman. 2009. Manajemen Perbankan.Bogor: Ghalia Indonesia.Indriantoro, dkk. 2002. Metodologi Penelitian Edisi 1. Yogyakarta: BPFE YogyakartaKasmir. 2015. Analisis Laporan Keuangan. Jakarta: PT Raja Grafindo Persada.Lestari, Putri Catur Ayu. 2015. Analisis Perbandingan Kinerja Fungsi Bisnis dan Fungsi Sosial pada Bank Muamalat Indonesia, Bank Syariah Mandiri, BRI Syariah dan Bank Mega Syariah Periode 2009-2013. Surabaya: Universitas AirlanggaLind, Douglas A, dkk. 2013. Teknik-teknik Statistika dalam Bisnis dan EkonomiMenggunakan Kelompok Data Global Edisi 13 Buku 1. Jakarta: Salemba EmpatMuhammad. 2005. Manaemen Dana Bank Syariah. Yogyakarta: EKONISIA.Rahman,A.R.A. dan Goddard, A. 1998. An Interpretive Inquiry of Accounting Practices in Religious Organisations. Financial Accountability and Management Vol 14. No. 3. Hal 184-190Rivai, Veithzal dan Arviyan Arifin. 2010. Islamic Banking: Sebuah Teori, Konsep, dan Aplikasi. Jakarta: Bumi Aksara.Setiawan, Azis Budi. 2009. Kesehatan Finansial dan Kinerja Sosial Bank Syariah di Indonesia. Seminar Ilmiah Kerjasama Magister Bisnis Keuangan Islam. Jakarta: Universitas ParamadinaSugiyono. 2012. Metode Penelitian Kuantitatif, Kualitatif, dan R&D. Cetakan ke-17. Bandung: CV AlfabetaSusanto, A.B. 2009. Reputation-Driven Corporate Social Responsibility: Pendekatan Strategic Management dalam CSR. Jakarta: Esensi Group Erlangga.